Romanticism in Pop Music Case Study of The Song ‘Birds of A Feather’ By Biliie Eilish - Fazar Sidik; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to investigate the impact and appearance of elements of Romanticism in contemporary pop music through an analysis of the song "Birds of a Feather" by Billie Eilish. By exploring the lyrics, melody, and atmosphere of the song, this research shows how central themes of Romanticism such as an emphasis on deep emotion, connection with nature, idealism, and individualism are visible in Eilish's work. This research provides a new perspective on how the aesthetic legacy of Romanticism still resonates and thrives in the modern pop music industry. I hope that this study will increase the understanding of how the influence of the Romanticism movement in the 19th century still exists and transforms in today's forms of artistic expression.